A comparative analysis exposes an amplification delay distinctive to SARS-CoV-2 Omicron variants of clinical and public health relevance - K.L. Brown; A. Ceci; C. Roby; R. Briggs; D. Ziolo; R. Korba; R. Mejia; S.T. Kelly; D. Toney; M.J. Friedlander; C.V. Finkielstein (Emerging Microbes and Infections)
Mutations in the SARS-CoV-2 genome may negatively impact a diagnostic test, have no effect, or turn into an opportunity for rapid molecular screening of variants. Using an in-house Emergency Use Authorized RT-qPCR-based COVID-19 diagnostic assay, we combined sequence surveillance of viral variants and computed PCR efficiencies for mismatched templates. We found no significant mismatches for the N, E, and S set of assay primers until the Omicron variant emerged in late November 2021. We found a single mismatch between the Omicron sequence and one of our assay’s primers caused a > 4 cycle delay during amplification without impacting overall assay performance.Starting in December 2021, clinical specimens received for COVID-19 diagnostic testing that generated a Cq delay greater than 4 cycles were sequenced and confirmed as Omicron. Clinical samples without a Cq delay were largely confirmed as the Delta variant. The primer-template mismatch was then used as a rapid surrogate marker for Omicron. Primers that correctly identified Omicron were designed and tested, which prepared us for the emergence of future variants with novel mismatches to our diagnostic assay's primers. Our experience demonstrates the importance of monitoring sequences, the need for predicting the impact of mismatches, their value as a surrogate marker, and the relevance of adapting one's molecular diagnostic test for evolving pathogens.